Traversing humans, animals, and yōkai: An exploration of posthumanist implications in Japanese folklore through selected stories from Japanese Legends and Folklore by A. B. Mitford and Japanese Folktales by Yei Theodora Ozaki - Yong, Lydia Pei Wen (2025)
Japanese folklore frequently portrays animals as active agents within human society, challenging anthropocentric assumptions that privilege human dominance. This study examines selected Japanese folktales through Cary Wolfe’s posthumanist framework to analyse representations of animals and human–animal relationships. The primary texts consist of selected fox (kitsune) and rabbit narratives from A. B. Mitford’s Japanese Legends and Folklore and Yei Theodora Ozaki’s Japanese Folktales. Using qualitative textual analysis, the study focuses on non-human agency, interspecies interaction, and ethical reciprocity within the narratives. The analysis demonstrates that animals are not portrayed merely as symbolic figures, but as autonomous beings capable of moral judgement, emotional response, and reciprocal engagement with humans. Motifs such as shapeshifting, revenge, gratitude, and coexistence consistently destabilise rigid human–animal hierarchies and challenge the notion of human exceptionalism. These findings suggest that Japanese folklore articulates posthumanist sensibilities that predate the formal development of posthumanist theory in Western academic discourse. By situating Japanese folktales within a posthumanist framework, this study expands the scope of posthumanist literary analysis beyond its predominantly Western focus and highlights traditional folklore as a critical site for rethinking human–nonhuman relations.